Transabdominal preperitoneal repair for an adolescent patient with Hunter syndrome: a case report - Yoichiro Tada; Manabu Yamamoto; Teppei Sunaguchi; Chihiro Uejima; Akimitsu Tanio; Yuki Murakami; Shuichi Takano; Teruhisa Sakamoto; Soichiro Honjo; Keigo Ashida; Hiroaki Saito; Yoshiyuki Fujiwara (Surgical Case Reports, 2019)
Abstract Background Hunter syndrome is an X-linked disorder caused by a deficit of the lysosomal enzyme iduronate-2-sulfatase and is associated with many disorders. Patients with Hunter syndrome often develop inguinal hernias in early childhood and undergo Potts’ method, laparoscopic percutaneous extraperitoneal closure (LPEC), or laparoscopic direct suture. Case presentation An 18-year-old male visited our hospital for evaluation of a palpable mass in the right groin hernia. Computed tomography revealed a right indirect inguinal hernia. He had a history of repeated admission to our hospital and pediatric treatments for pneumonia, heart failure, and convulsions after birth. Because he has stopped growing and a wide hernia orifice was present with no apparent hernia on the left side, we performed TAPP repair. During surgery, we noted softness of the abdominal wall, similar to children’s abdominal wall, and laparoscopy revealed well-developed veins around the spermatic cord and testicular artery. The softness of the abdominal wall made insertion of the trocars difficult and well-developed veins needed our special care to avoid hemorrhage. After surgery, the patient developed a convulsion due to Hunter syndrome and subsequent aspiration pneumonia; however, he recovered with medical treatments administered in cooperation with specialists and was discharged on postoperative day 9. Conclusion This is the first reported patient with Hunter syndrome whose inguinal hernia was treated by TAPP repair. TAPP repair might be a useful procedure even for adolescent patients with Hunter syndrome, although adequate care is needed for symptoms due to Hunter syndrome.